Expressed emotion (EE) in families of individuals at-risk of developing psychosis: A systematic review. (December 2018) - Izon, Emma; Berry, Katherine; Law, Heather; French, Paul
Highlights: High levels of criticism, hostility, warmth and EOI were found in the ARMS group. Levels of high-EE in ARMS were similar to that of FEP. More criticism and hostility was linked with poorer functioning and worse symptoms. Warmth and optimal family involvement improved functioning and reduced symptoms. High criticism and EOI negatively impacted family member's health. Abstract: The At-Risk Mental State (ARMS) for psychosis describes a state of high but not inevitable risk for developing a psychotic disorder. The distressing experiences for individuals with an ARMS may impact on themselves; their sense of wellbeing, psychosocial functioning and their family. Expressed emotion (EE) considers the environment and communication style of relatives towards the individual and is a key factor for determining outcomes in established psychosis. Following PRISMA guidelines, a systematic review of EE in relatives of ARMS was conducted. Fifteen studies were identified that investigated the presence of EE in the ARMS population. Approximately one third of ARMS relatives had high-EE. The results suggest that greater levels of criticism are associated with higher levels of symptoms and poorer functioning. In contradiction to psychosis literature, the construct emotional-over-involvement was found to be an adaptive response, where an optimal level of involvement combined with a warm-environment was associated with improved functioning and reduced symptoms. Limitations of the studies include small sample sizes and over-representation of Caucasian males and relatives as middle-aged mothers. Although approximately half of the studies included were longitudinal, only two measured EE over time, therefore, future research should include larger studies measuring EE at different time-points.